1989
DOI: 10.1126/science.2688091
|View full text |Cite
|
Sign up to set email alerts
|

The Anticodon Contains a Major Element of the Identity of Arginine Transfer RNAs

Abstract: The contribution of the anticodon to the discrimination between cognate and noncognate tRNAs by Escherichia coli Arg-tRNA synthetase has been investigated by in vitro synthesis and aminoacylation of elongator methionine tRNA (tRNA(mMet) mutants. Substitution of the Arg anticodon CCG for the Met anticodon CAU leads to a dramatic increase in Arg acceptance by tRNA(mMet). A nucleotide (A20) previously identified by others in the dihydrouridine loop of tRNA(Arg)s makes a smaller contribution to the conversion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 22 publications
2
72
1
Order By: Relevance
“…Normanly and Abelson (23) estimate that about half of the E. coli tRNAs utilize nucleotides outside of the anticodon to determine amino acid specificity. On the other hand, Schulman and Pelka (28,29) have shown that the anticodon is the major determinant for the identities of E. coli methionine, valine, and arginine tRNAs, and Muramatsu et al (22) provided evidence that the anticodon is also critical for determining the efficiency and specificity of charging E. coli isoleucine tRNA. The three anticodon nucleotides are also among the five bases that act as determinants for yeast phenylalanine tRNA identity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Normanly and Abelson (23) estimate that about half of the E. coli tRNAs utilize nucleotides outside of the anticodon to determine amino acid specificity. On the other hand, Schulman and Pelka (28,29) have shown that the anticodon is the major determinant for the identities of E. coli methionine, valine, and arginine tRNAs, and Muramatsu et al (22) provided evidence that the anticodon is also critical for determining the efficiency and specificity of charging E. coli isoleucine tRNA. The three anticodon nucleotides are also among the five bases that act as determinants for yeast phenylalanine tRNA identity (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible in vitro to alter a tRNA's amino acid charging identity by anticodon mutations (Schulman and Pelka 1989;Pallanck and Schulman 1991). It has also been shown that mutations outside the anticodon, for example, involving acceptor stem nucleotides that are strong identity determinants, can also effectively switch the identity of a tRNA (Hipps et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This tendency corresponds well to the fact that the A20 mutations of E. coli tRNA Arg mostly affected V max , rather than K m , in the arginylation (16). These results suggest that the A20 recognition mainly contributes to the ''enzyme activation,'' which may include changes in the spatial arrangement of important residues in the catalytic cleft and͞or the CCA terminus of the tRNA.…”
Section: Mutational Analyses Of the Argrsmentioning
confidence: 61%
“…In contrast, tRNA Arg utilizes an adenosine at position 20 for the nonanticodon major identity element, which is completely conserved among the tRNA Arg species in most organisms, and is missing in other tRNA species (14,15). Actually, genetic and biochemical studies of Escherichia coli tRNA Arg demonstrated that A20 is one of the major identity elements of tRNA Arg , with a very high discrimination rate of three orders of magnitude on average (14,(16)(17)(18)(19). A20 is located in a small, single-stranded region in the D loop at the outside corner of the L-shaped tRNA structure, which is far from both the anticodon and the acceptor stem.…”
mentioning
confidence: 99%